Menakar Peran Baznas Kota Semarang sebagai Implementasi Sustainable Development Goals (SDGs) pada Sektor Ekonomi: Measuring the Role of Baznas Semarang City as Implementation of Sustainable Development Goals (SDGs) in the Economic Sector - -, Akhmad Daeroby; Imam Mawardi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to determine the role of Semarang City Baznas in alleviating poverty and providing decent work as an implementation of Sustainable Development Goals points in the economic sector. This qualitative type of research uses data collection methods with interviews, observations, documentation, and literature review. The collected data is then analyzed using role theory to measure the harmony of roles and programs of the Semarang City BAZNAS with SDGs. In this case, the Semarang City Baznas has five programs; Semarang Smart; Semarang Prosperous; Semarang Cares; Semarang Healthy; and Semarang Taqwa. Based on measurements through the significance of institutional roles and impacts based on the zakat index and role theory analysis, it was found (1) Semarang City Baznas has an impact on the independence and economic improvement of Semarang City, especially during the Pandemic; (2) Baznas Semarang City not only plays a role in the economic sector but also becomes an extension of SDGs in the educational, social, and environmental sectors.